Changes in central and peripheral hemodynamic parameters during blood donation - Yazdani, Babak; Yücel, Gökhan; Schulz, Katrin; Kayser, Sabine; Shaygi, Behnam; Schumacher, Gerhard; Poschauko, Janine; Krämer, Bernhard K.; Duerschmied, Daniel; Hohneck, Anna (Frontiers in Cardiovascular Medicine, 2025)
BackgroundBlood donation is a common procedure, yet its acute effects on central and peripheral hemodynamics are not fully understood. This study aimed to systematically quantify immediate cardiovascular changes induced by whole blood donation in healthy adults, with a primary focus on arterial pressure and central hemodynamic parameters.MethodsThirty healthy volunteers (12 female, 18 male; median age 34 years, IQR 24–53) underwent standardized whole blood donation. Non-invasive measurements of central and peripheral hemodynamics were performed immediately before and after donation using the VascAssist 2 device, enabling assessment of brachial and aortic blood pressures, heart rate, augmentation index (AIx), pulse wave velocity (PWV), and left ventricular ejection time (LVET).ResultsBlood donation resulted in a significant reduction in brachial systolic blood pressure (SBP) [pre: 131 mmHg [IQR 121–138] vs. post: 127 mmHg [IQR 116–134]; median change −4mmHg, IQR −10 to 0; p = 0.002]. No statistically significant changes were observed in heart rate [pre: 72 bpm [IQR 68–80] vs. post: 74 bpm [IQR 64–81]; p = 0.82], diastolic blood pressure (DBP) [pre: 75 mmHg [IQR 68–81] vs. post: 74 mmHg [IQR 70–85]; p = 0.66], aortic SBP, or central PWV. Significant reductions were observed in augmentation index [AIx75: pre 1% [IQR −9 to 6] vs. post −5% [IQR −11 to 4]; p = 0.02] and LVET [pre: 244 ms [IQR 225–257] vs. post: 231 ms [IQR 215–243]; p = 0.0005]. No statistically significant correlations were identified between these hemodynamic responses and sex, age, body mass index, or hemoglobin concentration.ConclusionAcute whole blood donation induces a mild but statistically significant decrease in peripheral SBP, accompanied by reductions in AIx and LVET, while central aortic blood pressure and vascular stiffness remain unchanged. These findings indicate that healthy individuals exhibit immediate adaptive mechanisms that preserve central cardiovascular stability in response to mild volume depletion. The results support the overall hemodynamic tolerability of blood donation and provide insight into the transient vascular and cardiac adaptations elicited by acute blood loss.